Comparing Writing Strategies Used by High vs Low Achievers Students of Non-English Major - Handayany, Thea (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
This study aims to determine the writing strategies used by non-English speaking students and to compare the strategies of high and low achieving students in writing at the Faculty of Islamic Economics and Business, UIN Fatmawati Sukarno Bengkulu. This study uses a descriptive method with a quantitative approach. The sample in this study were 60 students from the faculties of business and Islamic economics. The research data was taken using a questionnaire with a total of 30 items related to writing strategies. From the results of the study, it was found that students used strategies more often at the revising stage, followed by the drafting stage and finally at the pre-writing stage. Then for a comparison of strategies by high and low achievers’ students, the results obtained were 17 students categorized as "high", 27 students categorized as "medium" and 16 students categorized as "low". High students tend to use strategies more often at the drafting stage followed by pre-writing and revising, while low students tend to use strategies at the revising stage, then drafting and pre-writing.exists at each writing stage because the average obtained is below 3.5.